All-ordered nanofiber structure battery capable of generating homogeneous reaction and preparation method and application of all-ordered nanofiber structure battery
By using fully ordered nanofiber structural materials in quasi-solid lithium-sulfur batteries, the problems of uneven transmission of lithium ions and uneven electric field distribution are solved, and the promotion of homogeneous reactions and uniform deposition of lithium metal are achieved, which significantly improves the battery cycle life.
Patent Information
- Application Number
- CN202411583285.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-07
AI Technical Summary
There are problems in quasi-solid lithium-sulfur batteries with uneven transmission of lithium ions, uneven electric field distribution and uneven reaction, resulting in uneven lithium deposition and peeling, reducing the cycle life of the battery.
Using all-ordered nanofiber structural materials as battery modules, lithium-philic modified orderly porous carbon hollow tubes and ordered nanofibers are prepared by electrospinning to establish a continuous, uniform and fast lithium ion transmission path, and promote lithium ion concentration and Even distribution of electric field.
The uniform transmission of lithium ions and the uniform distribution of electric field are achieved, the occurrence of homogeneous reactions is promoted, the uniform deposition and peeling of lithium metal is improved, the cycle life of the battery is extended, and the utilization rate of active materials is improved.
Smart Images

Figure CN119430137A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of quasi-solid-state lithium metal batteries, and more specifically relates to a fully ordered nanofiber structure battery with homogeneous reaction, and a preparation method and application thereof. Background Art
[0002] With the rapid development of renewable energy and electric vehicles, the demand for efficient and high energy density storage technology continues to increase. Lithium-sulfur batteries have a high energy density of 2600Wh kg -1 Sulfur is considered a strong contender for the next generation of energy storage devices due to its high theoretical energy density. In addition, sulfur has the advantages of low cost, abundant reserves and environmental protection. However, traditional organic liquid electrolytes (LEs) used in lithium-sulfur batteries have serious safety issues such as volatility and flammability, which increase the possibility of leakage and fire hazards. To address these issues, quasi-solid-state polymer electrolytes have been developed as a safer alternative. Quasi-solid-state polymer electrolytes provide high ionic conductivity, excellent interfacial compatibility, and strong mechanical strength can inhibit lithium dendrite growth and improve battery stability and life.
[0003] Quasi-solid-state lithium-sulfur batteries face several practical challenges, including poor conductivity of sulfur and lithium sulfide (Li2S), shuttle effects caused by dissolution and diffusion of lithium polysulfides (LiPSs), significant volume changes during charge and discharge, and inhomogeneous deposition and dissolution of lithium. To address these challenges, various attempts have been made, such as using functional nanofibers as separators to mitigate the shuttle effect of LiPSs, applying sulfided polyacrylonitrile as an alternative to elemental sulfur cathodes to reduce the formation of LiPSs, and developing three-dimensional porous carbon-based materials as hosts for lithium metal to buffer volume changes and inhibit dendrite growth. Although these strategies partially address some challenges of quasi-solid-state lithium-sulfur batteries, they still have significant limitations. In particular, the slow, discontinuous, and inhomogeneous flux of lithium ions leads to a large concentration gradient along the longitudinal direction of the electrode, inducing inhomogeneous reactions during battery cycling, which can lead to inhomogeneous lithium deposition and stripping, reduce the utilization of active materials, and ultimately affect the cycle life of the battery.
[0004] To mitigate the inhomogeneous reaction, it is essential to optimize the distribution of lithium ion flux within the battery. Recent studies have shown that highly ordered nanofibers enhance the uniformity of lithium ion flux and electric field distribution. 6.4 La3Zr2Al 0.2 O 12(LLZO) nanofibers are integrated into a polymer matrix to create an efficient lithium ion transport network while providing excellent mechanical stability when used as a separator. This design significantly improves the uniformity of electron and ion transport and effectively inhibits the growth of lithium dendrites. In addition, highly ordered structures have also been used to improve the electron / ion transport properties and mechanical flexibility of anode materials, thereby improving high-speed performance and cycle durability. These studies have shown that the addition of ordered nanofibers can significantly improve mechanical properties and establish a fast and uniform lithium ion flux path, alleviate concentration polarization, and effectively promote homogeneous reactions. However, it is worth noting that in these studies, only certain battery components used aligned nanofibers. Components lacking such an ordered structure will undoubtedly compromise the uniformity of lithium ion transport, resulting in uneven distribution of electric and stress fields within the battery, thereby reducing the overall performance of the battery.
[0005] Therefore, it is necessary to provide a new structure for quasi-solid-state lithium metal batteries that can promote uniform transmission of lithium ions and uniform distribution of electric fields throughout the battery, thereby promoting the occurrence of homogeneous reactions. Summary of the invention
[0006] The purpose of the present invention is to provide a fully ordered nanofiber structure battery with homogeneous reaction and its preparation method and application, so as to solve the problems existing in the above-mentioned prior art. The fully ordered nanofiber structure material provided by the present invention can be used as a battery component to promote rapid and uniform lithium ion transmission, so that the lithium ion concentration is more evenly distributed throughout the battery, thereby promoting the occurrence of homogeneous reaction.
[0007] To achieve the above object, the present invention provides the following solutions:
[0008] One of the technical solutions of the present invention is to provide a method for preparing a lithium-philic modified ordered porous carbon hollow tube, the steps comprising:
[0009] dissolving the carbon-forming polymer and the metal salt in N,N-dimethylformamide (DMF) to obtain a precursor solution;
[0010] The precursor solution is subjected to electrostatic spinning to obtain an ordered nanofiber membrane containing a metal salt;
[0011] After the metal organic framework layer is in situ grown on the ordered nanofiber membrane containing metal salt, the lithium-philic modified ordered porous carbon hollow tube is obtained by carbonization etching.
[0012] Furthermore, the carbon-forming polymer includes at least one of polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polystyrene (PS) and polyvinyl pyrrolidone (PVP).
[0013] Furthermore, the metal salt includes at least one of zinc acetate, cobalt acetate, silver acetate, nickel acetate and copper acetate.
[0014] Furthermore, the concentration of the carbon-forming polymer in the precursor solution is 8-12 wt %, and the concentration of the metal salt is 2-5 wt %.
[0015] Furthermore, the electrospinning parameters are: voltage 15-22 kV, flow rate 0.3-0.6 mL·h -1 , receiver distance 10 ~ 20cm, humidity control at ~ 40%, drum speed 2000 ~ 3000r·min -1 .
[0016] Furthermore, the step of in-situ growing the metal organic framework layer comprises:
[0017] The ordered nanofiber membrane containing metal salt is placed in a 2-methylimidazole solution to in-situ grow a metal organic framework on the surface of the fiber membrane.
[0018] Furthermore, the carbonization etching is performed in a nitrogen atmosphere, at a temperature of 700 to 1100°C, for a time of 2 to 6 hours, and at a heating rate of 2 to 5°C·min -1 .
[0019] The second technical solution of the present invention is to provide a lithium-philic modified ordered porous carbon hollow tube obtained by the above preparation method.
[0020] The lithium-philic modification in the lithium-philic modified ordered porous carbon hollow tube of the present invention comprises a metal-nitrogen coordination compound, metal nanoparticles or metal oxides, wherein the metal-nitrogen coordination compound is selected from at least one of Zn-N / O, Co-N, Ag-N and Ni-N, the metal nanoparticles are selected from at least one of zinc, cobalt, silver and nickel, and the metal oxide is selected from at least one of zinc oxide, copper oxide, tin dioxide and titanium dioxide.
[0021] Furthermore, the diameter of the lithium-philic modified ordered porous carbon hollow tube is 50 to 400 nm.
[0022] The third technical solution of the present invention is to provide an ordered porous carbon hollow tube-based lithium metal composite electrode, wherein the ordered porous carbon hollow tube-based lithium metal composite electrode comprises the above-mentioned lithiophilic-modified ordered porous carbon hollow tube and metallic lithium.
[0023] Technical solution 4 of the present invention: Provide a method for preparing the above-mentioned ordered porous carbon hollow tube-based lithium metal composite electrode, the steps comprising:
[0024] The ordered porous carbon hollow tube modified by lithium affinity is contacted with molten metal lithium, and the ordered porous carbon hollow tube-based lithium metal composite electrode is obtained after infiltration.
[0025] Furthermore, the temperature of the molten metallic lithium is 180-350°C.
[0026] Furthermore, the contact time is 5 to 30 seconds.
[0027] The fifth technical solution of the present invention: provides an application of the above-mentioned lithiophilic modified ordered porous carbon hollow tubes or ordered porous carbon hollow tube-based lithium metal composite electrodes in quasi-solid-state lithium metal batteries.
[0028] Technical solution six of the present invention: provides a lithium metal-sulfur battery, including: a positive electrode, a negative electrode and an electrolyte; the positive electrode is an ordered sulfurized nanofiber membrane; the negative electrode is the above-mentioned ordered porous carbon hollow tube-based lithium metal composite electrode; the electrolyte is an electrolyte in situ polymerized in an ordered nanofiber skeleton.
[0029] The lithium metal-sulfur battery prepared by the present invention has a fully ordered arrangement structure, and is composed of fully ordered nanofiber battery components, which can promote uniform transmission of lithium ions and uniform distribution of electric fields throughout the battery, thereby promoting the occurrence of homogeneous reactions, being beneficial to the uniform deposition and stripping of lithium metal and improving the utilization rate of active substances, and has extremely high application value in the field of high-performance quasi-solid-state lithium metal batteries.
[0030] Furthermore, the preparation steps of the ordered sulfurized nanofiber membrane include:
[0031] Using polymer as solute and N,N-dimethylformamide as solvent, ordered nanofiber membrane was obtained by electrospinning;
[0032] The ordered nanofiber membrane is mixed with a sulfur source and subjected to a sulfurization treatment to obtain the ordered sulfurized nanofiber membrane.
[0033] Preferably, the polymer includes at least one of polyacrylonitrile, polymethyl methacrylate, polystyrene and polyvinyl pyrrolidone; the ratio of the solute to the solvent is 0.8-1.2 g:10 mL; the parameters of the electrospinning are: voltage 18-24 kV, flow rate 0.6-1 mL·h -1 , receiver distance 10 ~ 20cm, humidity control at ~ 40%, drum speed 2000 ~ 3000r·min -1 ; The sulfur source includes one of sulfur powder, selenium sulfide and thiourea; the mass ratio of the ordered nanofiber membrane to the sulfur source is 1:3-8; the heating rate of the sulfurization treatment is 2-5°C·min -1 ; The temperature is 350-450°C and the time is 3-6h; the diameter of the ordered sulfide nanofibers in the ordered sulfide nanofiber membrane is 50-300nm.
[0034] Furthermore, the preparation steps of the electrolyte in situ polymerized in the ordered nanofiber skeleton include:
[0035] dissolving the monomer, the initiator and the lithium salt in an organic solvent to obtain an electrolyte precursor;
[0036] The electrolyte precursor is polymerized in situ to obtain an electrolyte polymerized in situ in the ordered nanofiber skeleton.
[0037] Preferably, the monomer is selected from at least one of polybutyl acrylate, polyethylene glycol diacrylate, pentaerythritol tetraacrylate and ethylene glycol diacrylate; the initiator is azobisisobutyronitrile; the lithium salt is at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethanesulfonyl imide (LiTFSI), lithium hexafluorophosphate (LiPF6) and lithium tetrafluoroborate (LiBF4); the organic solvent is selected from at least one of dimethyldimethoxysilane (DMDMS), ethylene glycol dimethyl ether (Glyme), dimethyl sulfoxide (DMSO) and dimethyldiethoxysilane (DMDES); the concentration of lithium salt in the electrolyte precursor is 0.5-3M, the mass fraction of the monomer is 2.5%, and the mass fraction of the initiator is 0.15%; the temperature of the in-situ polymerization is 60°C and the time is 12h.
[0038] The present invention establishes continuous, uniform and rapid lithium ion transport throughout the battery by designing a fully ordered nanofiber battery assembly. This design effectively improves lithium ion extraction / insertion kinetics, ensures uniform distribution of lithium ion concentration and electric field, promotes uniform reaction of anode and cathode, thereby achieving uniform deposition and stripping of metallic lithium, and maximizing the utilization of cathode materials, thereby significantly improving the cycle life of the battery, laying the foundation for the potential commercial application of lithium-sulfur batteries.
[0039] The present invention discloses the following technical effects:
[0040] The invention adopts electrostatic spinning to prepare lithium-philic-modified ordered porous carbon hollow tubes, ordered nanofibers, and ordered sulfurized nanofibers, which has the advantages of being simple, efficient, easy to operate, and low in cost.
[0041] The lithium-philic modified ordered porous carbon hollow tube prepared by the present invention serves as a carrier of metallic lithium, has a directional electron transmission channel, a uniform nucleation site, promotes uniform deposition of metallic lithium, inhibits the growth of lithium dendrites, and can adapt to the volume change of the negative electrode during the charge and discharge cycle; the electrolyte polymerized in situ in the ordered nanofiber skeleton has a directional and uniform transmission path; the ordered sulfurized nanofiber has a uniform sulfur distribution. The lithium metal-sulfur battery prepared from the above materials has a fully ordered arrangement structure, which provides a continuous and rapid lithium ion transmission path in the entire battery, promotes the uniform distribution of lithium ion flux, reduces concentration polarization, and is conducive to the occurrence of homogeneous reactions, thereby promoting the uniform deposition and stripping of lithium metal and improving the utilization rate of active materials.
[0042] The fully ordered nanofiber structure that undergoes homogeneous reaction provided in the present invention is applied to quasi-solid-state lithium metal (lithium metal-sulfur battery), and the battery exhibits the characteristics of high specific capacity and excellent cycle stability, indicating that the fully ordered nanofiber structure provided by the present invention has important application prospects in the field of high-performance quasi-solid-state lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0044] Figure 1 is a SEM image of the ordered porous carbon hollow tube modified by Zn-N / O and Co-N in Example 1;
[0045] Figure 2 Mapping diagram of ordered porous carbon hollow tubes modified by Zn-N / O and Co-N in Example 1;
[0046] Figure 3 This is a SEM image of the electrolyte precursor after in-situ polymerization in Application Example 1;
[0047] Figure 4 This is the mapping diagram of the ordered sulfurized nanofiber membrane in Application Example 1;
[0048] Figure 5 The electrochemical performance diagram of the quasi-solid-state lithium metal full battery in Application Example 1;
[0049] Figure 6 The electrochemical performance of the quasi-solid-state lithium metal symmetrical battery assembled with the composite electrode as the positive and negative electrodes in Example 1 and Comparative Example 1;
[0050] Figure 7 It is the SEM image of the disordered porous carbon hollow tube modified by Zn-N / O and Co-N in Comparative Example 1;
[0051] Figure 8 Mapping diagram of the disordered porous carbon hollow tube modified by Zn-N / O and Co-N in Comparative Example 1;
[0052] Fig. 9 This is a test chart of the charge and discharge performance of the quasi-solid-state lithium metal full battery at a 0.1C rate for Application Example 1 and Comparative Application Example 1. DETAILED DESCRIPTION
[0053] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0054] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0055] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0056] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0057] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0058] Unless otherwise specified, the room temperature in the specific embodiments of the present invention refers to 20-30°C.
[0059] Example 1
[0060] The preparation steps of ordered porous carbon hollow tube-based lithium metal composite electrode are as follows:
[0061] S1. Dissolve 500 mg PAN in 5 mL DMF to obtain a uniform solution A; then add 945 mg Zn(CH3COO)2 and 55 mg Co(CH3COO)2 to 5 mL DMF and stir evenly to obtain a solution B; evenly mix solution A and solution B to obtain an electrospinning precursor solution;
[0062] S2. Transfer the electrospinning precursor solution into a 10 mL syringe and inject it at 0.4 mL h-1 at 18 kV. -1 The electrospinning was performed at a flow rate of 1.50 μm, the distance between the needle (24 G) and the collector was set to 15 cm, the humidity during electrospinning was controlled at 40%, and the rotating drum collector was set to 3000 r·min -1 , and then put the electrospun product into an oven at 60°C and dry it for 12 h to obtain an ordered nanofiber membrane containing metal salts;
[0063] S3, the ordered nanofiber membrane containing 30 mg of metal salt was added to 20 mL of anhydrous ethanol solution of 2-methylimidazole (concentration of 0.04 wt%), and then kept at room temperature for 12 h to grow a BMZIF layer on the ordered nanofibers. The ordered nanofiber membrane with the BMZIF layer was washed three times with anhydrous ethanol, and then transferred to a 70 ° C vacuum drying oven for 3 h to remove the anhydrous ethanol, and then placed in a tube furnace and heated at 2 ° C min under a nitrogen atmosphere. -1 The temperature was raised to 350 °C and calcined for 2 h, followed by heating at 2 °C·min -1 The temperature was raised to 700℃ and calcined for 3h to obtain ordered porous carbon hollow tubes modified with Zn-N / O and Co-N.
[0064] S4. Using high-purity argon protection, melt the metallic lithium (230°C) in a glove box, contact the ordered porous carbon hollow tube carrier modified by Zn-N / O and Co-N with the molten metallic lithium (10s), and the molten metallic lithium spontaneously infiltrates into the pores of the hollow tube. After cooling, an ordered porous carbon hollow tube-based lithium metal composite electrode (ordered porous carbon hollow tube-based lithium metal composite electrode modified by Zn-N / O and Co-N) is obtained.
[0065] Application Example 1
[0066] Preparation of lithium metal-sulfur batteries (quasi-solid-state lithium metal full batteries):
[0067] S1. Dissolve 1 g PAN in 10 mL DMF and stir for 12 h to form a uniform precursor solution. Transfer the precursor solution to a syringe and inject at 0.8 mL h at 20 kV. -1Electrospinning was performed at a flow rate of 3000 r·min (receiving distance: 15 cm; needle specification: 24G; humidity ~40%). -1 The electrospun membrane obtained at the speed was dried at 80 °C overnight to obtain an ordered nanofibrous membrane;
[0068] S2. The ordered nanofiber membrane prepared in step S1 is placed on sulfur powder at a mass ratio of 1:4, and calcined at 450°C for 3 h in a tubular furnace filled with nitrogen atmosphere at a heating rate of 2°C min -1 , forming an ordered sulfurized nanofiber membrane;
[0069] S3, dissolving PETEA (pentaerythritol tetraacrylate) monomer, AIBN (azobisisobutyronitrile) initiator and LiFSI in DMMS to prepare an electrolyte precursor; in the electrolyte precursor, the concentration of LiFSI is 1.5M, the concentration of PETEA is 2.5wt%, and the concentration of AIBN is 0.15wt%;
[0070] S4. Assembling a quasi-solid-state lithium metal full battery: using the ordered porous carbon hollow tube-based lithium metal composite electrode prepared in Example 1 as the working electrode (negative electrode), the ordered nanofiber membrane in step S1 as the separator, the ordered sulfide nanofiber membrane in step S2 as the counter electrode (positive electrode), and the electrolyte precursor in step S3 as the electrolyte (60 μL) to assemble a 2025 button battery, which is then placed in an oven at 60°C for 12 hours for in-situ polymerization of the electrolyte precursor to obtain a quasi-solid-state lithium metal full battery.
[0071] Example 2
[0072] The preparation steps of ordered porous carbon hollow tube-based lithium metal composite electrode are as follows:
[0073] S1. Dissolve 500 mg PAN in 5 mL DMF to obtain a uniform solution A; then add 1005 mg Zn(CH3COO)2 and 95 mg Ni(CH3COO)2 to 5 mL DMF and stir evenly to obtain a solution B; evenly mix solution A and solution B to obtain an electrospinning precursor solution;
[0074] S2. Transfer the electrospinning precursor solution into a 10 mL syringe and inject it at 0.4 mL h-1 at 18 kV. -1 The electrospinning was performed at a flow rate of 1.50 μm, the distance between the needle (24 G) and the collector was set to 15 cm, the humidity during electrospinning was controlled at 40%, and the rotating drum collector was set to 3000 r·min -1 , and then put the electrospun product into an oven at 60°C and dry it for 12 h to obtain an ordered nanofiber membrane containing metal salts;
[0075] S3, the ordered nanofiber membrane containing 50 mg of metal salt was added to 20 mL of anhydrous ethanol solution of 2-methylimidazole (concentration of 0.06 wt%), and then kept at room temperature for 12 h to grow a BMZIF layer on the ordered nanofibers. The ordered nanofiber membrane with the BMZIF layer was washed three times with anhydrous ethanol, and then transferred to a 70 ° C vacuum drying oven for 3 h to remove the anhydrous ethanol, and then placed in a tube furnace and heated at 2 ° C min under a nitrogen atmosphere. -1 The temperature was raised to 350 °C and calcined for 2 h, followed by heating at 2 °C·min -1 The temperature was raised to 700℃ and calcined for 3h to obtain ordered porous carbon hollow tubes modified with Zn-N / O and Ni-N.
[0076] S4. The metallic lithium was melted (230°C) in a glove box under the protection of high-purity argon, and the ordered porous carbon hollow tube carrier modified by Zn-N / O and Ni-N was contacted with the molten metallic lithium (8s). The molten metallic lithium spontaneously infiltrated into the pores of the hollow tubes, and after cooling, an ordered porous carbon hollow tube-based lithium metal composite electrode (ordered porous carbon hollow tube-based lithium metal composite electrode modified by Zn-N / O and Ni-N) was obtained.
[0077] Application Example 2
[0078] Preparation of lithium metal-sulfur batteries (quasi-solid-state lithium metal full batteries):
[0079] S1. Dissolve 1 g PAN in 10 mL DMF and stir for 12 h to form a uniform precursor solution. Transfer the precursor solution to a syringe and inject at 0.8 mL h at 20 kV. -1 Electrospinning was performed at a flow rate of 3000 r·min (receiving distance: 15 cm; needle specification: 24G; humidity ~40%). -1 The electrospun membrane obtained at the speed was dried at 80 °C overnight to obtain an ordered nanofibrous membrane;
[0080] S2. The ordered nanofiber membrane prepared in step S1 is placed on sulfur powder at a mass ratio of 1:4, and calcined at 450°C for 3 h in a tubular furnace filled with nitrogen atmosphere at a heating rate of 2°C min -1 , forming an ordered sulfurized nanofiber membrane;
[0081] S3, dissolving PETEA (pentaerythritol tetraacrylate) monomer, AIBN (azobisisobutyronitrile) initiator and LiFSI in DMMS to prepare an electrolyte precursor; in the electrolyte precursor, the concentration of LiFSI is 2M, the concentration of PETEA is 2.5wt%, and the concentration of AIBN is 0.15wt%;
[0082] S4. Assembling a quasi-solid-state lithium metal full battery: using the ordered porous carbon hollow tube-based lithium metal composite electrode prepared in Example 1 as the working electrode (negative electrode), the ordered nanofiber membrane in step S1 as the separator, the ordered sulfide nanofiber membrane in step S2 as the counter electrode (positive electrode), and the electrolyte precursor in step S3 as the electrolyte (60 μL) to assemble a 2025 button battery, which is then placed in an oven at 60°C for 12 hours for in-situ polymerization of the electrolyte precursor to obtain a quasi-solid-state lithium metal full battery.
[0083] Example 3
[0084] The preparation steps of ordered porous carbon hollow tube-based lithium metal composite electrode are as follows:
[0085] S1. Dissolve 500 mg PAN in 5 mL DMF to obtain a uniform solution A; then add 745 mg Zn(CH3COO)2 and 255 mg CH3COOAg to 5 mL DMF and stir evenly to obtain a solution B; evenly mix solution A and solution B to obtain an electrospinning precursor solution;
[0086] S2. Transfer the electrospinning precursor solution into a 10 mL syringe and inject it at 0.4 mL h-1 at 18 kV. -1 The electrospinning was performed at a flow rate of 1.50 μm, the distance between the needle (24 G) and the collector was set to 15 cm, the humidity during electrospinning was controlled at 40%, and the rotating drum collector was set to 3000 r·min -1 , and then put the electrospun product into an oven at 60°C and dry it for 12 h to obtain an ordered nanofiber membrane containing metal salts;
[0087] S3, the ordered nanofiber membrane containing 100 mg of metal salt was added to 20 mL of anhydrous ethanol solution of 2-methylimidazole (concentration of 0.08 wt%), and then kept at room temperature for 12 h to grow a ZIF layer on the ordered nanofibers. The ordered nanofiber membrane with the ZIF layer was washed three times with anhydrous ethanol, and then transferred to a 70 ° C vacuum drying oven for 3 h to remove the anhydrous ethanol, and then placed in a tube furnace and heated at 2 ° C min under a nitrogen atmosphere. -1 The temperature was raised to 350 °C and calcined for 2 h, followed by heating at 2 °C·min -1 The temperature was raised to 700℃ and calcined for 3h to obtain ordered porous carbon hollow tubes modified with Zn-N / O and Ag-N.
[0088] S4. The metallic lithium was melted (230°C) in a glove box under the protection of high-purity argon, and the ordered porous carbon hollow tube carrier modified by Zn-N / O and Ag-N was contacted with the molten metallic lithium (6s). The molten metallic lithium spontaneously infiltrated into the pores of the hollow tubes, and after cooling, an ordered porous carbon hollow tube-based lithium metal composite electrode (ordered porous carbon hollow tube-based lithium metal composite electrode modified by Zn-N / O and Ag-N) was obtained.
[0089] Application Example 3
[0090] Preparation of lithium metal-sulfur batteries (quasi-solid-state lithium metal full batteries):
[0091] S1. Dissolve 1 g PAN in 10 mL DMF and stir for 12 h to form a uniform precursor solution. Transfer the precursor solution to a syringe and inject at 0.8 mL h at 20 kV. -1 Electrospinning was performed at a flow rate of 3000 r·min (receiving distance: 15 cm; needle specification: 24G; humidity ~40%). -1 The electrospun membrane obtained at the speed was dried at 80 °C overnight to obtain an ordered nanofibrous membrane;
[0092] S2. The ordered nanofiber membrane prepared in step S1 is placed on sulfur powder at a mass ratio of 1:4, and calcined at 450°C for 3 h in a tubular furnace filled with nitrogen atmosphere at a heating rate of 2°C min -1 , forming an ordered sulfurized nanofiber membrane;
[0093] S3, dissolving PETEA (pentaerythritol tetraacrylate) monomer, AIBN (azobisisobutyronitrile) initiator and LiFSI in DMMS to prepare an electrolyte precursor; in the electrolyte precursor, the concentration of LiFSI is 3M, the concentration of PETEA is 2.5wt%, and the concentration of AIBN is 0.15wt%;
[0094] S4. Assembling a quasi-solid-state lithium metal full battery: using the ordered porous carbon hollow tube-based lithium metal composite electrode prepared in Example 1 as the working electrode (negative electrode), the ordered nanofiber membrane in step S1 as the separator, the ordered sulfide nanofiber membrane in step S2 as the counter electrode (positive electrode), and the electrolyte precursor in step S3 as the electrolyte (60 μL) to assemble a 2025 button battery, which is then placed in an oven at 60°C for 12 hours for in-situ polymerization of the electrolyte precursor to obtain a quasi-solid-state lithium metal full battery.
[0095] Example 4
[0096] Compared with Example 1, the only difference is that "2℃·min -1 The temperature was raised to 700 °C and calcined for 3 h at a rate of 2 °C min -1The temperature was raised to 900°C and calcined for 3h.
[0097] Application Example 4
[0098] Preparation of lithium metal-sulfur batteries (quasi-solid-state lithium metal full batteries):
[0099] Same as Application Example 1.
[0100] Example 5
[0101] Compared with Example 1, the only difference is that "2℃·min -1 The temperature was raised to 700 °C and calcined for 3 h at a rate of 2 °C min -1 The temperature was raised to 1100°C and calcined for 3h.
[0102] Application Example 5
[0103] Preparation of lithium metal-sulfur batteries (quasi-solid-state lithium metal full batteries):
[0104] Same as Application Example 1.
[0105] Comparative Example 1
[0106] The preparation steps of disordered porous carbon hollow tube-based lithium metal composite electrode are as follows:
[0107] S1. Dissolve 500 mg PAN in 5 mL DMF to obtain a uniform solution A; then add 945 mg Zn(CH3COO)2 and 55 mg Co(CH3COO)2 to 5 mL DMF and stir evenly to obtain a solution B; evenly mix solution A and solution B to obtain an electrospinning precursor solution;
[0108] S2. Transfer the electrospinning precursor solution into a 10 mL syringe and inject it at 0.4 mL / min under 18 kV high voltage. -1 The electrospinning was performed at a flow rate of 1.50 μm, the distance between the needle (24 G) and the collector was set to 15 cm, the humidity during electrospinning was controlled at 40%, and the rotating drum collector was set to 300 r·min -1 , and then put the electrospun product into an oven at 60°C and dry it for 12 h to obtain a disordered nanofiber membrane containing metal salts;
[0109] S3, the disordered nanofiber membrane containing 30 mg of metal salt was added to 20 mL of anhydrous ethanol solution of 2-methylimidazole (concentration of 0.04 wt%), and then kept at room temperature for 12 h to grow a BMZIF layer on the disordered nanofibers. The disordered nanofiber membrane with the BMZIF layer was washed three times with anhydrous ethanol, and then transferred to a 70 ° C vacuum drying oven for 3 h to remove the anhydrous ethanol, and then placed in a tube furnace and heated at 2 ° C min under a nitrogen atmosphere.-1 The temperature was raised to 350 °C and calcined for 2 h, followed by heating at 2 °C·min -1 The temperature was raised to 700℃ and calcined for 3h to obtain Zn-N / O and Co-N modified disordered porous carbon hollow tubes.
[0110] S4. Under high-purity argon protection, the metallic lithium is melted (230°C) in a glove box, and the disordered porous carbon hollow tube carrier modified by Zn-N / O and Co-N is contacted with the molten metallic lithium (16s). The molten metallic lithium spontaneously infiltrates into the pores of the hollow tube, and after cooling, a disordered porous carbon hollow tube-based lithium metal composite electrode (disordered porous carbon hollow tube-based lithium metal composite electrode modified by Zn-N / O and Co-N) is obtained.
[0111] Comparative application example 1
[0112] Preparation of lithium metal-sulfur batteries (quasi-solid-state lithium metal full batteries):
[0113] S1. Dissolve 1 g PAN in 10 mL DMF and stir for 12 h to form a uniform precursor solution. Transfer the precursor solution to a syringe and inject at 0.8 mL h at 20 kV. -1 Electrospinning was performed at a flow rate of 300 r·min (receiving distance: 15 cm; needle specification: 24G; humidity ~40%). -1 The electrospun membrane obtained at a rotation speed was dried at 80 °C overnight to obtain a disordered nanofibrous membrane;
[0114] S2. The disordered nanofiber membrane prepared in step S1 is placed on sulfur powder at a mass ratio of 1:4, and calcined at 450°C for 3 h in a tubular furnace filled with nitrogen atmosphere at a heating rate of 2°C min -1 , forming a disordered sulfurized nanofiber membrane;
[0115] S3, dissolving PETEA (pentaerythritol tetraacrylate) monomer, AIBN (azobisisobutyronitrile) initiator and LiFSI in DMMS to prepare an electrolyte precursor; in the electrolyte precursor, the concentration of LiFSI is 1.5M, the concentration of PETEA is 2.5wt%, and the concentration of AIBN is 0.15wt%;
[0116] S4. Assembling a quasi-solid-state lithium metal full battery: using the disordered porous carbon hollow tube-based lithium metal composite electrode prepared in Comparative Example 1 as the working electrode (negative electrode), the disordered nanofiber membrane in step S1 as the separator, the disordered sulfide nanofiber membrane in step S2 as the counter electrode (positive electrode), and the electrolyte precursor in step S3 as the electrolyte (60 μL) to assemble a 2025 button battery, which is then placed in an oven at 60°C for 12 hours for in-situ polymerization of the electrolyte precursor to obtain a quasi-solid-state lithium metal full battery.
[0117] Test example
[0118] Figure 1 This is the SEM image of the ordered porous carbon hollow tubes modified by Zn-N / O and Co-N in Example 1. It can be seen from the figure that the porous carbon hollow tubes show an orderly arrangement trend and the diameter is about 300 nm.
[0119] Figure 2 This is a mapping diagram of the ordered porous carbon hollow tubes modified by Zn-N / O and Co-N in Example 1. It can be seen from the figure that zinc and cobalt are evenly distributed on the ordered porous carbon hollow tubes.
[0120] Figure 3 This is a SEM image of the electrolyte precursor after in-situ polymerization in Application Example 1. It can be seen from the image that the surface of the electrolyte membrane after in-situ polymerization with ordered polyacrylonitrile nanofibers as the skeleton is smooth.
[0121] Figure 4 This is the mapping diagram of the ordered sulfurized nanofiber membrane in Application Example 1. It can be seen from the figure that the fibers are arranged in an orderly manner and the sulfur is evenly distributed on the nanofibers.
[0122] The electrochemical performance of the quasi-solid-state lithium metal full battery obtained in Application Example 1 was tested at room temperature. The results are as follows Figure 5 shown.
[0123] Figure 5 This is the electrochemical performance diagram of the quasi-solid-state lithium metal full battery in Application Example 1. It can be seen from the figure that when the ordered porous carbon hollow tube-based lithium metal composite electrode modified by Zn-N / O and Co-N is used as the negative electrode, the electrolyte in situ polymerized in the ordered polyacrylonitrile nanofiber skeleton, and the ordered sulfurized polyacrylonitrile nanofiber positive electrode are assembled into a lithium-sulfur full battery, the charge and discharge performance test at 1C rate shows that the capacity can reach 1096 mAh g -1 This fully ordered nanofiber structure with homogeneous reaction significantly promotes the uniform deposition of lithium metal and glass stripping, and improves the utilization of active materials.
[0124] The composite electrodes prepared in Example 1 and Comparative Example 1 were used as positive and negative electrodes to assemble a quasi-solid-state lithium metal symmetrical battery. The electrochemical performance test results are as follows: Figure 6 shown.
[0125] Figure 6 The electrochemical performance of the quasi-solid-state lithium metal symmetrical battery assembled with the composite electrodes as positive and negative electrodes in Example 1 and Comparative Example 1 can be seen from the figure. When tested at 25°C, the symmetrical battery assembled with the ordered porous carbon hollow tube-based lithium metal composite electrode in Example 1 has a current density of 0.5 mA cm -2 0.5 mAh cm -2Metallic lithium has a smaller polarization voltage and an ultra-long cycle life.
[0126] Figure 7 This is the SEM image of the disordered porous carbon hollow tube modified by Zn-N / O and Co-N in Comparative Example 1. It can be seen from the figure that the disordered nanofibers are randomly arranged and have a tubular structure with a diameter of about 350 nm.
[0127] Figure 8 This is the mapping diagram of the disordered porous carbon hollow tubes modified by Zn-N / O and Co-N in Comparative Example 1. It can be seen from the figure that zinc and cobalt are distributed on the porous carbon hollow tubes, but due to the random arrangement of the fibers, the distribution is uneven.
[0128] Fig. 9 The charge and discharge performance test diagrams of the quasi-solid-state lithium metal full battery of Application Example 1 and Comparative Application Example 1 at 0.1C rate show that the fully ordered nanofiber structure full battery with homogeneous reaction has higher capacity and longer cycle performance at 0.1C, which is attributed to the continuous and fast lithium ion transmission path provided by the fully ordered nanofiber structure, which is conducive to the uniform distribution of lithium ion flux, reduces concentration polarization, promotes uniform lithium metal deposition / stripping, and improves the utilization of active materials.
[0129] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0130] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a lithium-philic modified ordered porous carbon hollow tube, characterized in that the steps include: dissolving a carbon-forming polymer and a metal salt in N,N-dimethylformamide to obtain a precursor solution; The precursor solution is subjected to electrostatic spinning to obtain an ordered nanofiber membrane containing a metal salt; After the metal organic framework layer is in situ grown on the ordered nanofiber membrane containing metal salt, the lithium-philic modified ordered porous carbon hollow tube is obtained by carbonization etching.
2. The preparation method according to claim 1, characterized in that The carbon-forming polymer comprises at least one of polyacrylonitrile, polymethyl methacrylate, polystyrene and polyvinyl pyrrolidone; and / or The metal salt comprises at least one of zinc acetate, cobalt acetate, silver acetate, nickel acetate and copper acetate; and / or The concentration of the carbon-forming polymer in the precursor solution is 8-12 wt %, and the concentration of the metal salt is 2-5 wt %; and / or The electrospinning parameters are: voltage 15-22 kV, flow rate 0.3-0.6 mL·h -1 , receiver distance 10 ~ 20cm, humidity control at ~ 40%, drum speed 2000 ~ 3000r·min -1 ; and / or The carbonization etching is carried out in a nitrogen atmosphere, at a temperature of 700 to 1100° C., for 2 to 6 hours, at a heating rate of 2 to 5° C. min. -1 ; and / or The step of in-situ growing a metal organic framework layer comprises: placing the ordered nanofiber membrane containing metal salt in a 2-methylimidazole solution to in-situ grow a metal organic framework on the surface of the fiber membrane.
3. A lithium-philic modified ordered porous carbon hollow tube obtained by the preparation method as claimed in claim 1 or 2.
4. An ordered porous carbon hollow tube-based lithium metal composite electrode, characterized in that: The ordered porous carbon hollow tube-based lithium metal composite electrode comprises the lithiophilic-modified ordered porous carbon hollow tubes as described in claim 3 and metallic lithium.
5. The method for preparing an ordered porous carbon hollow tube-based lithium metal composite electrode according to claim 4, characterized in that the steps include: The ordered porous carbon hollow tube modified by lithium affinity is contacted with molten metal lithium, and the ordered porous carbon hollow tube-based lithium metal composite electrode is obtained after infiltration.
6. Use of the lithiophilic-modified ordered porous carbon hollow tube as claimed in claim 3 or the ordered porous carbon hollow tube-based lithium metal composite electrode as claimed in claim 4 in a quasi-solid-state lithium metal battery.
7. A lithium metal-sulfur battery comprising: A positive electrode, a negative electrode and an electrolyte, characterized in that the positive electrode is an ordered sulfide nanofiber membrane; the negative electrode is an ordered porous carbon hollow tube-based lithium metal composite electrode as described in claim 4; and the electrolyte is an electrolyte polymerized in situ within an ordered nanofiber skeleton.
8. The lithium metal-sulfur battery according to claim 7, characterized in that The steps of preparing the ordered sulfurized nanofiber membrane include: using a polymer as a solute and N,N-dimethylformamide as a solvent to obtain an ordered nanofiber membrane by electrostatic spinning; mixing the ordered nanofiber membrane with a sulfur source and subjecting the ordered nanofiber membrane to a sulfurization treatment to obtain the ordered sulfurized nanofiber membrane; and / or The preparation steps of the electrolyte polymerized in situ in the ordered nanofiber skeleton include: dissolving monomers, initiators and lithium salts in an organic solvent to obtain an electrolyte precursor; and polymerizing the electrolyte precursor in situ to obtain the electrolyte polymerized in situ in the ordered nanofiber skeleton.
9. The lithium metal-sulfur battery according to claim 8, characterized in that In the preparation steps of the ordered sulfurized nanofiber membrane: The polymer comprises at least one of polyacrylonitrile, polymethyl methacrylate, polystyrene and polyvinyl pyrrolidone; and / or The solute and solvent are used in a ratio of 0.8 to 1.2 g:10 mL; and / or The electrospinning parameters are: voltage 18-24 kV, flow rate 0.6-1 mL·h -1 , receiver distance 10 ~ 20cm, humidity control at ~ 40%, drum speed 2000 ~ 3000r·min -1 ; and / or The sulfur source comprises one of sulfur powder, selenium sulfide and thiourea; and / or The mass ratio of the ordered nanofiber membrane to the sulfur source is 1:3-8; and / or The temperature rise rate of the vulcanization treatment is 2 to 5°C·min -1 , temperature is 350~450℃, time is 3~6h.
10. The lithium metal-sulfur battery according to claim 8, characterized in that In the preparation step of the electrolyte in situ polymerized in the ordered nanofiber framework: The monomer is selected from at least one of polybutyl acrylate, polyethylene glycol diacrylate, pentaerythritol tetraacrylate and ethylene glycol diacrylate; and / or The initiator is azobisisobutyronitrile; and / or The lithium salt is at least one of lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonyl imide, lithium hexafluorophosphate and lithium tetrafluoroborate; and / or The organic solvent is selected from at least one of dimethyldimethoxysilane, ethylene glycol dimethyl ether, dimethyl sulfoxide and dimethyldiethoxysilane; and / or The concentration of lithium salt in the electrolyte precursor is 0.5-3M, the mass fraction of the monomer is 2.5%, and the mass fraction of the initiator is 0.15%; and / or The in-situ polymerization was carried out at a temperature of 60° C. and for 12 hours.
Citation Information
Patent Citations
Compound organic solid electrolyte with multiple Li<+> conduction paths and preparation method thereof
CN108539260A
Polymer nanofiber metal lithium composite negative electrode with double lithium affinity and preparation method thereof
CN114068872A
Amorphous stannous sulfide / nitrogen-doped carbon composite directional tubular material as well as preparation method and application thereof
CN115692689A
Composite solid electrolyte and preparation method and application thereof
CN116598580A
Production process for alkali metal-sulfur batteries having high volumetric and gravimetric energy densities
US20170207488A1